3D printing by selective laser sintering of polypropylene feed channel spacers for spiral wound membrane modules for the water industry. Issue 3 (2nd July 2016) - Tan, Wen See; Chua, Chee Kai; Chong, Tzyy Haur; Fane, Anthony G.; Jia, An
ABSTRACT: Feed spacers are net-like structures present in spiral wound membrane modules (SWM) used for treatment of water and wastewater. Feed spacers require appropriate stiffness to support the membrane sheets without damaging and puncturing the membrane surfaces. They also need to be flexible enough to be rolled up around the central permeate tube forming the SWM. Polypropylene (PP) is the commercially used material for feed spacers due to its flexibility and excellent chemical resistance properties. In this paper, selective laser sintering (SLS) is used to investigate the printability of net-typed structures using PP materials to represent feed spacers. SLS processing parameters such as layer thickness, part bed temperature, energy density and scan pattern were studied and net-typed PP spacers were successfully fabricated. However, an analysis on tensile test and dimensional accuracy shows that Young's modulus of the PP material tends to be correlated to the accuracy of the dimensions of the net-typed spacer prototypes.